2012
DOI: 10.1186/1471-2466-12-50
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in ADRB2 gene can modulate the response to bronchodilators and the severity of cystic fibrosis

Abstract: BackgroundThe most common cystic fibrosis (CF) manifestation is the progressive chronic obstructive pulmonary disease caused by deficiency, dysfunction, or absence of the CFTR (Cystic Fibrosis Transmembrane Regulator) protein on the apical surface of the cells in the respiratory tract. The use of bronchodilators (BD), and inhaled corticosteroids (IC) have been suggested for the management of airway inflammation in CF. The effectiveness of BD and IC have been verified, proven in laboratory and in the clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…( 9 , 15 ) The F508del mutation is a class II mutation (causing misprocessed/misfolded CFTR proteins), and it is associated with higher clinical severity of CF. ( 9 ) …”
Section: Introductionmentioning
confidence: 99%
“…( 9 , 15 ) The F508del mutation is a class II mutation (causing misprocessed/misfolded CFTR proteins), and it is associated with higher clinical severity of CF. ( 9 ) …”
Section: Introductionmentioning
confidence: 99%
“…Other genes were studied in the same CF reference center with same population as previously published [11,13,14]. The GSTM1 and GSTT1 genes were studied in our center considering other CF patients as recent published data showed [12].…”
Section: Methodsmentioning
confidence: 99%
“…In our group, as previously published, multiple genes are associated with CF clinical severity, including Transforming growth factor beta 1 ( TGF - β1 ) [11], Glutathione S-transferase Mu 1 ( GSTM1 ), Glutathione S-transferase Theta 1 ( GSTT1 ) [12], Angiotensin-converting enzyme ( ACE ) [13] and Beta-2-Adrenergic Receptor ( ADBR2 ) [14] genes as possibly modifier genes. In the same population the mannose-binding lectin (protein C) 2 ( MBL2 ) and monocyte differentiation antigen CD14 ( CD14 ) genes were not associated with the CF clinical severity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of disease is also dependent on the CFTR mutations, environmental factors and modifier genes [3][4][5][6][7][8][9][10][11][12][13][14]. Studies to understand the observed variation have been performed, and in the present data the ADIPOR2 gene and its variations was considered.…”
Section: General Aspectsmentioning
confidence: 99%
“…Our group has studied the clinical modulation of CF by candidate modifier genes that influence drug responses, the evolution of the lung and digestive disease in CF, and CF-related comorbidities [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%